2011
DOI: 10.1103/physrevlett.106.083003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Raman Enhancement of Organic Adsorbates on Metal Surfaces

Abstract: Using first-principles theory and experiments, chemical contributions to surface-enhanced Raman spectroscopy for a well-studied organic molecule, benzene thiol, chemisorbed on planar Au(111) surfaces are explained and quantified. Density functional theory calculations of the static Raman tensor demonstrate a strong mode-dependent modification of benzene thiol Raman spectra by Au substrates. Raman active modes with the largest enhancements result from stronger contributions from Au to their electron-vibron coup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
167
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(184 citation statements)
references
References 30 publications
15
167
2
Order By: Relevance
“…Zayak and colleagues have confirmed that the intense electron exchange in the interface is beneficial to chemical enhancement. 65 In addition, we are surprised to find that the deformation density is obviously increased in the area between the core atom and the connected metal atom, especially for the W@Ag 12 -Py complex, although the change is most evident in all complexes. Yet, compared with complexes based on the Mo atom as the core, complexes using the W atom as the core show conspicuous improvement of the deformation density in the area between the core atom and the connected metal atom.…”
Section: Resultsmentioning
confidence: 93%
“…Zayak and colleagues have confirmed that the intense electron exchange in the interface is beneficial to chemical enhancement. 65 In addition, we are surprised to find that the deformation density is obviously increased in the area between the core atom and the connected metal atom, especially for the W@Ag 12 -Py complex, although the change is most evident in all complexes. Yet, compared with complexes based on the Mo atom as the core, complexes using the W atom as the core show conspicuous improvement of the deformation density in the area between the core atom and the connected metal atom.…”
Section: Resultsmentioning
confidence: 93%
“…[46][47][48] Following previous that previous work, resonant signal in Eq. (1) should be proportional to the square of the Raman polarizability derivative, |( dα i j dQ k ) 2 | 2 .…”
Section: Surface Effectsmentioning
confidence: 99%
“…At present, most of the research advantages for SERS in the analysis of gaseous and vapor phases are based on simple chemical sorption of analytes on a highly developed silver or gold surface if they have high affinity to plasmonic nanoparticles being, for example, thiol derivatives or other similar molecules [11,13,14,19,20,25,27,29]. Accordingly, the sensitivity of the analysis becomes even higher if porous silver nanocubes [12], polymer coatings [15], anisotropic nanoparticle aggregates [16,24], metal -organic frameworks [21,26], multihole capillaries [23], graphene oxide surface [28], free -surface microfluidic chips [18], electrodynamic precipitation [17] are applied.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, ordinary materials for SERS with ecological, pharmaceutical, biological and medical applications are commonly designed for the analysis of liquid analytes [1][2][3][4][5][6][7][8][9][10] while a limited number of actual research efforts has focused on vapor phase detection [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The latter challenge evidently widens the promising application area of SERS and therefore requires novel approaches for the design of SERS-active materials.…”
Section: Introductionmentioning
confidence: 99%